Planning of Implementation Schedules using CPM and PERT Methods in The Office Construction Project of Dipatiunus Tangerang Banten - Khumaedi; Rifaldi Adi Saputra (International Journal Labs, 2025)
Construction delays remain a recurring issue in infrastructure development in Indonesia due to inadequate scheduling and time mismanagement. This study investigates time optimization in the Dipati Unus Office construction project in Tangerang, Banten, by applying the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT). The objective is to analyze and compare the scheduling effectiveness of both methods to minimize delays and identify critical work activities. This research adopts a case study approach using primary data from field observations and interviews, and secondary data from project documentation such as S-curves, daily reports, and schedules. Data were analyzed using Microsoft Project 2024 to identify critical paths and calculate project durations. The CPM analysis revealed 32 critical tasks with a total duration of 97 days, while PERT produced a shorter estimated duration of 90 days with a 54% probability of on-time completion. The findings demonstrate that both methods are effective for time management, but PERT offers more flexibility under uncertainty. The study implies that integrating CPM and PERT with digital planning tools can significantly improve project scheduling accuracy and execution efficiency. These insights can support future planning strategies in medium-scale construction projects.